Avaliando o portfólio do estudante na Atenção Primária à Saúde: uma contribuição no processo de ensino-aprendizagem para os cursos de Medicina e de Enfermagem - Neves, Andressa Soares de Camargo das (2013)
Introduction and rationale: The active learning methods require evaluation processes consistent with the new professional profile. The use of the portfolio has been touted as one of the most recent contributions to facilitate formative assessment and summative effective, being considered by the Association for Supervision and Curriculum as one of the three best methods of teaching and learning. Objectives: Analyze a Questionnaire Assessment of Student Portfolio in the Area of Primary Health and creating an adapted version of the instrument for the use of students and teachers FCMS-PUC/SP. Material and Methods: A quantitative and qualitative accomplished through the application of an Instrument for Analysis that evaluated and adapted the content of the Evaluation Questionnaire Student Portfolio for Area Primary Health Care This instrument was based on a Likert Scale 4 and 6 categories and was answered by the judges FAIMER and teachers of courses in Medicine and Nursing FCMS / PUC-SP working in the area of Primary Health used the technique of structured group interview, recorded by audio students of 2nd year courses in Medicine and Nursing in order to analyze their perception of the definition of the term portfolio, advantages and disadvantages of their use and possible suggestions for better preparation and evaluation of your portfolio. Results: The Assessment Questionnaire Student Portfolio was analyzed by judges and teachers and its initial content was revised and adapted to the reality of the FCMS / PUC-SP. The score of the Likert Scale showed a level of 0.8 to 0.9 reliability (Cronbach's alpha). The evaluation criteria of the portfolio listed by teachers were: presentation of the portfolio, student performance, reflection and theory-practice clinical reasoning. It was reported by students in portfolio preparation difficulties and difficulties in correcting the teachers' portfolios, suggesting the need for training in the subject, a standardized assessment instrument portfolio and a script by making the student portfolio